A TELENURSING SERVICE'S IMPACT ON COVID-19 PATIENTS: LITERATURE REVIEW - Purwanti, Tentry Fuji; Peristiowati, Yuly; Ellina, Agusta Dian; Fajriah, Asuria Sani (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Pandemic Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by SARS-COV2. COVID-19 has become a world pandemic that poses various risks throughout the world such as an increase in the number of patients and the risk of disease development in the world health system, especially nursing. The WHO reports that technology has a growing role in education and good work practice. Telenursing is well defined as the application of telecommunications and information technology to provide remote nursing practice. Purpose: This study aimed to examine the process of establishing a telenursing service for COVID-19. Methods: Three databases”PubMed, Google Scholar, and Research Gate”were used to find research publications. English-language keywords included in the literature search are telenursing OR tele-nursing and Covid-19, with the inclusion of works from 2019 to 2021. Results: Five studies that matched the inclusion criteria and the goals of this literature review were examined from a total of 936 research articles. Following the critical evaluation of five articles, a simplified thematic analysis was performed. This research review's main finding was that non-contact counseling services, instruction, and nursing care are important. Conclusion: Application of the telenursing program improved information technology and enabled the delivery of nursing care remotely. As an additional treatment option for patients with COVID-19, other remote self-care instruction techniques may be applied.